Forecasting the unemployment rate in Malaysia using ARIMA models - Bahrom, Suhaila; Sies, Eszleen; Khairol Azmi, Nurul Nisa’; Abdul Wahab, Nurul Aini (Karya Ilham Publishing, 2026)
Considerable fluctuations in Malaysia’s labour market have been driven by both global economic uncertainties and domestic transformations. Events such as the COVID-19 pandemic exposed the labour markets to certain vulnerabilities. Gaps remain in the literature regarding the continuous validation of forecasting models of the unemployment trend in the presence of extreme events such as COVID-19, particularly over extended and post-pandemic periods. It is essential to develop an